External application with Traditional Chinese Medicine in prevention of postoperative fever in patient undergoing surgery for obstructive sleep apnea-hypopnea syndrome (中药敷贴预防阻塞性睡眠呼吸暂停低通气综合征患者术后发热的效果) - YE Yuquan (叶玉泉) (Journal of International Translational Medicine Limited, 2021)
Objective To observe the effect of external application with Traditional Chinese Medicine in prevention of postoperative fever (＞38 ℃) in patient undergoing surgery for obstructive sleep apnea-hypopnea syndrome. Methods Totally 118 patients undergoing bilateral tonsillectomy/adenoidectomy were randomly divided into the study group and the control group, with 59 cases in each group. All patients received routine care after surgery, and those in the study group were given external application with Traditional Chinese Medicine. The incidence of postoperative fever (＞38 ℃) was compared between two groups. Results The incidence of postoperative fever (＞38 ℃) in the study group was 28. 81%(17/59), lower than 35. 59%(21/59) in the control group, with no significant difference (P＞0. 05). Conclusion External application with Traditional Chinese Medicine is potentially effective to reduce the risk of postoperative fever in patient undergoing surgery for obstructive sleep apnea-hypopnea syndrome. (目的 观察中药敷贴预防阻塞性睡眠呼吸暂停低通气综合征(OSAHS)术后发热(术后体温＞38 ℃)的效果。方法 选取行双侧扁桃体切除术/腺样体切除治疗的OSAHS患者118例为研究对象, 术后将患者随机分为研究组和对照组, 各59例。对照组采用常规护理干预, 研究组在对照组基础上增加中药敷贴。对比2组患者临床发热(术后体温＞38 ℃)发生率。结果 研究组术后发热(体温＞38 ℃)的发生率为28. 81%(17/59), 低于对照组的35. 59%(21/59), 但差异无统计学意义(P＞0. 05)。结论 采用中药敷贴对降低OSAHS患者术后发热(体温＞38℃)发生风险具有积极意义, 有利于促进术后康复进程。)